2015
DOI: 10.1037/cpb0000042
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in the wild: Identifying factors that lead to success.

Abstract: Although executive coaching has been shown to be effective, few research initiatives have attempted to understand the importance of the emergent relationship between a coach and coachee. This article explores the factors that influence coaching outcomes from both the coach and coachee’s perspective and presents the results of the mediating effect that working alliance and information sharing have on coachee goal attainment and coachee insight outcomes. The authors explored these factors in both an academic coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 115 publications
2
67
0
6
Order By: Relevance
“…Bowles et al [ 61 ] found that coachee buy-in was positively linked with growth in leadership competencies but had no impact on participant performance. However, a more recent study, Sonesh et al [ 55 ], found in a group of executive coachees that client motivation was not correlated with the coachee outcome variables of insight and goal attainment. Remarkably, the authors had run the same study with a group of undergraduate students and executive MBA coaches and found a considerably different result.…”
Section: Resultsmentioning
confidence: 99%
“…Bowles et al [ 61 ] found that coachee buy-in was positively linked with growth in leadership competencies but had no impact on participant performance. However, a more recent study, Sonesh et al [ 55 ], found in a group of executive coachees that client motivation was not correlated with the coachee outcome variables of insight and goal attainment. Remarkably, the authors had run the same study with a group of undergraduate students and executive MBA coaches and found a considerably different result.…”
Section: Resultsmentioning
confidence: 99%
“…For employers benefits for the organisation include; increased productivity (Olivero, Denise Bane, & Kopelman, 1997), acting as a support mechanism for other training programs (Wales, 2003), and improvements to communication (Graham, Wedman, & Garvin-Kester, 1993) and effectiveness of organisations or teams (Hagen & Garvrilova Aguilar, 2012). There are also suggested outcomes that benefit both the coachee and the employer and these include; improvements in interpersonal dynamics/teamwork (Hagen & Garvrilova Aguilar, 2012), higher levels of motivation (Sonesh et al, 2015), increased job satisfaction/job retention/company loyalty (Ellinger, Ellinger, & Keller, 2003;Olivero et al, 1997), increased skill levels (Wales, 2003), able to deal with stressful situations more effectively and improved leadership and management.…”
Section: Research Question 1: Benefits or Outcomes Of Coachingmentioning
confidence: 99%
“…These limitations included a heavy reliance on self-reported outcomes and a lack of control groups suggesting that it is was not possible to clearly link coaching to outcomes (Theeboom et al, 2014), stronger effects for coachee perceptions of the quality of the coach-coachee relationship than for other sorts of goals or outcomes and stronger effects for student samples than for executive and other non-academic samples (Sonesh et al, 2015) and lower effect sizes for multi-source feedback measures (R. Jones et al, 2015). Taken as a whole these reviews suggest that under certain very specific conditions some positive relationships can be detected between coaching and individual benefits.…”
Section: The Practical and Theoretical Development Of Business Coachingmentioning
confidence: 99%
See 2 more Smart Citations